1997
DOI: 10.1007/bf01246165
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of boron nitride on graphite at 1300 K

Abstract: Abstract.A method for the deposition of BN onto graphite and other substrates is described. Boron tricbloride (BC13) and ammonia (NH3) diluted with Ar were used as reacting gases. The deposition process was carried out at 1300 K as well as lower temperatures in an open system at pressures of 1 arm. The consequences of the introduction of hydrogen to the system were considered. It was demonstrated that the replacement of argon with hydrogen increases the efficiency of the process as well as the theoretical rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…X-ray measurements after the experiments showed a (MnO + Ln 2 O 3 + LnMnO 3 ) three-phase mixture present in the working electrode. It confirmed that the cell worked under three-phase equilibrium condition described by the reaction (6), and no side reaction occurred during the cell operation. Our results derived for the stability of LnMnO 3 phases (with Ln = Yb, Ho, and Er) can be compared with those of Atsumi et al A very good agreement is obtained between previous results and those derived in this work.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…X-ray measurements after the experiments showed a (MnO + Ln 2 O 3 + LnMnO 3 ) three-phase mixture present in the working electrode. It confirmed that the cell worked under three-phase equilibrium condition described by the reaction (6), and no side reaction occurred during the cell operation. Our results derived for the stability of LnMnO 3 phases (with Ln = Yb, Ho, and Er) can be compared with those of Atsumi et al A very good agreement is obtained between previous results and those derived in this work.…”
Section: Discussionsupporting
confidence: 81%
“…The change in the standard Gibbs free energy of the oxidation of MnO to Mn 2 O 3 based on the data of Robie and Hemingway [13] was given in our previous paper [7]. When it is added to equation (7), and then (8) and (9), one can obtain for the reactions: The results derived in our earlier studies [4][5][6][7] are also shown in this figure. The values of the enthalpy change are almost identical for phases with Yb, Ho, and Er, but higher by about 10 kJ than enthalpies obtained for reaction (10) in systems with Nd, Sm, Gd which, by the way, are also almost identical.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The flux of reactants to the deposition substrate is proportional to the concentration of the limiting precursor, which has the further advantage of allowing simple control of the magnitude of the growth rate [13]. At higher temperatures (region III, 1000~1200 °C), the growth rate decreases because of an increased desorption rate, depletion of reactants on reactor walls, and especially the enhanced gas phase nucleation, which can drastically reduce the permeability and uniformity of BN deposited in fiber preform [14]. Besides, the intensive decomposition of NH 3 at over high temperatures can also lead to a decline in the growth rate.…”
Section: Resultsmentioning
confidence: 99%